2009
DOI: 10.3348/kjr.2009.10.6.596
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Effect and Hepatotoxicity of a Hexokinase II Inhibitor 3-Bromopyruvate: In Vivo Investigation of Intraarterial Administration in a Rabbit VX2 Hepatoma Model

Abstract: ObjectiveThe purpose of this study was to compare the antitumor effect and hepatotoxicity of an intraarterial delivery of low-dose and high-dose 3-bromopyruvate (3-BrPA) and those of a conventional Lipiodol-doxorubicin emulsion in a rabbit VX2 hepatoma model.Materials and MethodsThis experiment was approved by the animal care committee at our institution. VX2 carcinoma was implanted in the livers of 36 rabbits. Transcatheter intraarterial administration was performed using low dose 3-BrPA (25 mL in a 1 mM conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Some small molecules such as 3-BP and lonidamine are direct inhibitors of HK enzyme. Preclinical studies demonstrate that 3-BP inhibits HK II in human cancer and is a promising anticancer drug targeting glycolysis [148, 149]. Lonidamine has completed phase III clinical trials in breast and lung cancers, and a trend for higher tumor responses and better survival parameters was observed when combined with chemotherapy [150, 173].…”
Section: Potential Targets For Tumor Therapymentioning
confidence: 99%
“…Some small molecules such as 3-BP and lonidamine are direct inhibitors of HK enzyme. Preclinical studies demonstrate that 3-BP inhibits HK II in human cancer and is a promising anticancer drug targeting glycolysis [148, 149]. Lonidamine has completed phase III clinical trials in breast and lung cancers, and a trend for higher tumor responses and better survival parameters was observed when combined with chemotherapy [150, 173].…”
Section: Potential Targets For Tumor Therapymentioning
confidence: 99%
“…[92] More recent studies on animal models of human hepatoma reported a limited antitumor efficacy of 22 in vivo, which was associated to a certain hepatotoxicity. [93] At the present, there are no human ongoing clinical trials involving 22 , probably because of the lack of selective cytotoxic effects associated to its administration, as well as the low economic potential of this non patentable molecule.…”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…HKI is the ubiquitously ex pressed isoform, whereas HKII is ex pressed in insulinsensitive tissues such as muscle and adipose (Robey and Hay, 2006). Many tumor cells overexpress HKII, and preclinical studies demonstrate that HKII inhibition could be an effective cancer therapy (Jae et al, 2009).…”
Section: Targets For Cancer Therapymentioning
confidence: 99%